Realisation and evaluation of the web based instruction courseware: Turkey example - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
As educators are increasingly using and developing courseware to use with their students, it gets more important to understand how high quality courseware should be designed, developed and used. In this study, based on this idea, a web based instructional design for Electronics course was developed for the vocational high school Electronics Department grade 2. In this study, the purpose is to present the development and evaluation process of the courseware and to support the creation of quality designs. The study was based on the survey model. A scale called Technical and Pedagogical Bases of Web Based Instruction was developed by the researchers to assess the instructional design and this scale was applied to the educators teaching this course. The scope of the study is the teachers in electricity, electronics and computer departments in Vocational and Anatolian Vocational-Technical High Schools in Istanbul city. Simple random selection method was used and 8 of the 11 schools were selected as sample. Web based instruction design was decided to be put into effect the revision based on the findings obtained. Future researches should investigate perceived differences in the learning experience between a face-to-face versus an online environment.
Keywords: Courseware design; courseware development; evaluation of courseware; instructional design; web based instruction